Reticulocyte count: comparison among methods - Karina Augusta Viana; Olindo Assis Martins Filho; Luci Maria Sant'Ana Dusse; Renato Sathler Avelar; Danielle Marquete Vitelli Avelar; Beatriz Carvalho; Claudia Maria Franco Ribeiro; Lis Ribeiro do Valle Antonelli; Andrea Teixeira; Maria das Graças Carvalho (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: The automated counting of reticulocytes has some advantages over the manual method routinely used in clinical laboratories. Technological innovations provide more statistically reliable results, while optimizing the time to perform this test. However, the cost for implementing the automated procedure in laboratory routines still constitutes a barrier to its use in small- and medium-size Brazilian laboratories. Objective: This study evaluated the performance of a new laboratory protocol for reticulocyte counting by flow cytometry using acridine orange (FC/AO), compared with the manual method and with another automated one by flow cytometry using the commercial kit BD Retic-Count (FC/RC) Conclusion: The results showed that, besides being comparable to the manual method, still considered standard, the evaluated new protocol is economically more advantageous than the automated methods currently available, and its cost is comparable to that of the manual method for laboratories that already have appropriate equipment and infrastructure.